Sowing gender policies, cultivating agrarian change, reaping inequality? Intersections of gender and class in the context of marshland transformations in Rwanda - Johanna Treidl (Antropologia, 2018)
Gender equality has become one of the top priorities throughout the political agenda of Post-Genocide Rwanda. A set of legal reforms, which aim at securing women’s land rights, together with the worldwide highest percentage of female parliamentarians have earned the government a lot of respect from the international donor community. At the same time, the state’s eager involvement in transforming the countryside into a modern, large-scale production zone, steers in a different direction: Vulnerable groups – among them many single mothers, poor or female headed households – are gradually excluded from this promising path of empowerment. By focusing on the lived experiences of rural women, this paper illustrates how intersections of class-related risk management, gendered labour tasks, and different livelihood strategies rub up against the Rwandan vision of agrarian change. “Gender equality” thereby remains first and foremost a frequently used buzzword in political discourse.